Sistemas agroflorestais vs agricultura convencional: avaliação da sustentabilidade em comunidades de agricultura familiar no Baixo Sul da Bahia - Coqueijo, Samara de Lima (2019)
The southern of Bahia state has an important Atlantic Rainforest reserve with the presence of endemic species and rich biodiversity. This research was carried out in four agroecosystems in Dandara dos Palmares and Limoeiro settlement, in southern lowlands of Bahia and its main objective was to evaluate the sustainability of agroforestry systems – investigated SAFs and its ability to promote local development in comparison to conventional production systems. The specific objectives were: a) to rescue the history of SAFs emergence in the properties; b) to make a socioeconomic and environmental analysis of the productive units and communities surveyed; and c) to verify the changes occurred after the SAFs implementation. The methodology used to evaluate and compare the sustainability of agroecosystems was the Framework for the Evaluation of Natural Resource Management Systems incorporating Sustainability Indicators -MESMIS. MESMIS is a flexible and holistic method that encourages the participation of farmers throughout the evaluation process. Bibliographic review, field research, application of semi-structured interviews and laboratory analysis were the tools used for data collection. Eight environmental indicators, nine social indicators and nine environmental indicators were selected. The evaluation results of these twenty-six indicators have shown that the SAFs evaluated are more sustainable than conventional systems, and they have proved to be a viable alternative to mitigate environmental problems and bring food security to family farmers. The lack of public policies aimed at smallholder farmers that produce agro-ecologically was seen as the main obstacle to spread these practices.